Aspek Hukum Hak Kepemilikan di atas Laut - Cobi Elisabeth M Mamahit; Josepus J Pinori; Donna Okthalia Setiabudhi; Toar K.R. Palilingan; Sofyan Piyo (CV Rewang Rencang, 2025)
The issuance of Land Ownership Certificates in Indonesian maritime areas presents significant administrative legal issues due to the lack of alignment between land and maritime law. According to the Basic Agrarian Law and maritime regulations, sea areas cannot be privately owned. The issuance of SHAT in maritime areas, especially without proper reclamation procedures, potentially violates the principle of legality. Conflicts of authority between the National Land Agency (BPN) and the Ministry of Marine Affairs and Fisheries frequently arise, resulting in legal uncertainty and significant ecological impacts. Regulatory harmonization and stricter oversight are required to ensure environmental sustainability and social justice.